THE ROLE OF GROWTH HORMONE IN LIPID METABOLISM - Dewi Ratnayanti, I Gusti Ayu (Medicina, 2013)
Growth hormone (GH) is one of the hormones that regulate metabolism, including lipid metabolism. GH can regulate the amount of fat in the tissue and also the level of lipid profile. Growth hormone affects the lipid in the tissue and blood by modulating the lipid metabolism, especially through the regulation of synthesis, excretion and breakdown of internal lipids. Research showed that GH could consistently lower the level of total cholesterol and LDL, whereas its effect on triglyceride and HDL level showed varying results. Growth hormone induces lypolisis by stimulating the activity of HSL and LPL and thereby influenced the triglyceride level and tissue fat storage. Cholesterol and lipoprotein levels are controlled by regulating the synthesis of cholesterol by lowering the activity of HMGCoA reductase. The excretion of cholesterol through the bile is also enhanced by stimulating the activity of enzymes C7?OH. The breakdown of VLDL and LDL are enhanced by increasing the expression of LDL receptor and ApoE as well as affecting the editing of mRNA ApoB100. Increase activity of LPL is also known to be the important factor in the HDL metabolism
Keywords: growth hormone, lipid metabolism